2016
DOI: 10.48550/arxiv.1612.06815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lagrangian $L$-stability of Lagrangian Translating Solitons

Abstract: In this paper, we prove that any Lagrangian translating soliton is Lagrangian L-stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The stability of soliton solutions to mean curvature flow under certain weighted volume functional was first studied by Colding-Minicozzi [7] for shrinking solitons in hypersurface case, and generalized to higher codimensional case by Andrews-Li-Wei [1], Arezzo-Sun [2], and Lee-Lue [16], but note that their functional ("entropy") is different from the f -volume functional. For stability of translating solitons, the second variation formula for translating hypersurfaces under f -volume was obtained by Xin in [35], Shahriyari [28] studied the stability of graphical translating surfaces in R 3 , and Yang [38] and Sun [30] studied the Lagrangian translating solitons. In particular, Yang [38] proved that every Lagrangian translating soliton is Hamiltonian f -stable, and Sun [30] showed that they are actually Lagrangian f -stable.…”
Section: F -Stability Of F -Minimal Lagrangians and Lmcf Solitonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of soliton solutions to mean curvature flow under certain weighted volume functional was first studied by Colding-Minicozzi [7] for shrinking solitons in hypersurface case, and generalized to higher codimensional case by Andrews-Li-Wei [1], Arezzo-Sun [2], and Lee-Lue [16], but note that their functional ("entropy") is different from the f -volume functional. For stability of translating solitons, the second variation formula for translating hypersurfaces under f -volume was obtained by Xin in [35], Shahriyari [28] studied the stability of graphical translating surfaces in R 3 , and Yang [38] and Sun [30] studied the Lagrangian translating solitons. In particular, Yang [38] proved that every Lagrangian translating soliton is Hamiltonian f -stable, and Sun [30] showed that they are actually Lagrangian f -stable.…”
Section: F -Stability Of F -Minimal Lagrangians and Lmcf Solitonsmentioning
confidence: 99%
“…For stability of translating solitons, the second variation formula for translating hypersurfaces under f -volume was obtained by Xin in [35], Shahriyari [28] studied the stability of graphical translating surfaces in R 3 , and Yang [38] and Sun [30] studied the Lagrangian translating solitons. In particular, Yang [38] proved that every Lagrangian translating soliton is Hamiltonian f -stable, and Sun [30] showed that they are actually Lagrangian f -stable.…”
Section: F -Stability Of F -Minimal Lagrangians and Lmcf Solitonsmentioning
confidence: 99%
“…Translating surfaces characterize the type II finite singularity of mean curvature flow in Euclidean space (see [2], [3] and [13]). Some geometric properties were investigated in [1,20,10,4,19] etc.…”
Section: Introductionmentioning
confidence: 99%